Circuitos elétricos: uma proposta de ensino concebida com base na teoria da formação por etapas das ações mentais e dos conceitos de galperin - Damaceno, José Aécio Vieira (2020)
The electrical circuits are part of the content of Physics in high school, however, as shown by the systematic review carried out in the main magazines of Physics Education in Brazil, in the bank of Professional Master's theses in Physics Teaching of the consolidated universities in this area have demonstrated that there is a lack of studies that contemplate contents of residential electrical installations directly related to electrical circuits. This work, carried out within the scope of the National Professional Master's Degree in Physics Teaching (MNPEF), at the center of the Federal Rural University of the Semi-Arid (UFERSA), in the city of Mossoró, located in Rio Grande do Norte, presents a didactic sequence , addressing the following contents: electric current; Ohm's laws; Resistors association; Electrical power in circuits, measurements of electrical quantities such as: electrical voltage (potential difference) and current intensity. Galperin's (2009) texts were adopted as a theoretical framework; Vygotsky (1998); Vygotsky; Luria; Leontiev (2018); Nuñez; Pacheco (1998); Nuñez; Ramalho (2018); and guidelines of the National Curriculum Parameters for Secondary Education - PCNEM (Brasil, 2002). Its implementation took place in the Physics laboratory of the Colégio Estadual Liceu de Caucaia, in Caucaia, Ceará, with two classes of the third night year, through the realization of five meetings, with two classes each, making a total of ten classes. The didactic sequence was designed through motivating, dynamic, participatory and interactive classes, mediated by the teacher's intervention, in order to provide students with meaningful learning, valuing, above all, their previous knowledge. Understanding the scientific concepts of physical quantities, such as electric current, power, resistance, energy, among others, is of paramount importance for students, whether in the professional field, or in their daily practices. It was observed in the results of the activities developed that the objectives and strategies developed for the didactic sequence were successful, comparing the results of the pre-tests and post-tests performed by the students